Rainwater harvesting opportunities: water resource sustainability - Fazillah S. N. A. (2024)
This study aims to identify the degree of which factors contribute to the rainwater quality and understanding anthropogenic contributions to the atmospheric environment. A total of 1830 rainwater data were collected from rain gauge stations distributed all over the country. Factor analysis were applied to the studied variables to evaluate the physicochemical composition of rainwater samples in Malaysia. The results showed that the extracted four components accounted for 43.45% of the total variance. The source of ionic components was found to be mainly originated from sea salt ions, while biomass burning indicated it was the primary source of anthropogenic activities in the study area. Low heavy metal concentration were detected in the rainwater samples. Generally, the rainwater in the study area was of good rainwater quality and less affected by anthropogenic activities. Some variables were identified to influence the variability of rain, hence affecting the variability of rainwater in the study area, including magnesium, sodium, chloride, ammonium, potassium, nitrate, sulphate, nickel, formate and iron. The variability of these components caused in acidity and conductivity in rainwater samples. This study provides a basis for the rational utilisation of rainwater for peoples’ lives, thus maintaining the sustainability of water resources in the environment. Additional research is needed to identify the index of rainwater quality and determine the uses for each index level.